(untitled) (World Bulletin of Management and Law, 2024)
Natural gas is the mainstay of efficient and environmentally friendly energy. Indicators of rationality and efficiency of energy consumption - this is the energy efficiency of the house. These indicators are influenced by the economy of heating, lighting, water supply, ventilation, and what energyefficient materials and equipment were used in the construction of the house